A pharmacoeconomic study using the willingness to pay model for postexposure prophylaxis for animal bites at a public sector tertiary referral center - Parida, Roopa; Gogtay, Nithya Jaideep; Chaudhari, Vijaya Laxman; Rakshit, Ananya; Mane, Balaji; Bhoir, Prachi V.; Mokalkar, Vipin Subhash (Perspectives in clinical research, 2025)
Abstract Context: Rabies is a neglected, vaccine-preventable, zoonotic, viral disease that affecting the central nervous system. Understanding its economic burden will aid in developing strategies to reduce mortality. Aims: The aims of this study were to assess willingness to pay (WTP) for postexposure prophylaxis (PEP) for anti-rabies vaccination (ARV). Setting and Design: This was a a cross-sectional, interview based, pharmacoeconomic study. Subjects and Methods: After ethics approval and written informed consent, patients visiting the institute for PEP were enrolled and explained the bidding game strategy, and details of their socioeconomic strata (SES) were collected. Participants were asked regarding the WTP with a predecided starting bid amount of Indian rupees (INR) 2500/- for complete ARV. Based on their first response, this amount was either reduced or increased by INR 500/- until a final WTP reached. This was similarly done for travel and supporting medications. Statistical Analysis Used: Both descriptive and inferential (regression) statistics were applied. WTP was taken as the dependent variable, whereas demographic and animal bite-related parameters were taken as independent covariates. All analyses were done at 5% significance. Results: A total of n = 426 patients were enrolled. Of these, 255/426 (60%) patients were of Category III, whereas the remainder 171/426 (40%) were of Category II. Most of the patients (n = 306/426 [72%]-ARV, n = 270/426 [63%]-traveling and n = 277/426 [65%]-supporting medications) choose less than the bidding amount for all three aspects studied. Regression analysis showed that higher SES when the bite was from a dog and transdermal bites were significantly associated with a higher WTP. Conclusion: Lower socioeconomic strata are associated with lower WTP. Although this is challenging to address, raising awareness about completing vaccinations is crucial, as rabies is 100% fatal once the central nervous system is affected and clinical symptoms appear.